The Relationship Between Midwife Communication And Pregnant Women's Satisfaction Towards Anc Services At The Cecar Public Health Center, Musi Rawas District - Tri Asih; Kintan Anissa; Indra Iswari (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
Intoduction: To achieve the MDGs, midwives are at the forefront of maternal and child health services in the community and are required to consistently provide the best and highest quality care. Research by the World Health Organization (WHO) indicates that 70-80% of errors in healthcare are caused by poor communication and a lack of understanding among healthcare team members. Effective communication between medical and non-medical healthcare teams can reduce patient safety issues (WHO, 2021). Method: This research used an analytical cross-sectional design. It was conducted at the Cecar Community Health Center in December 2025. The sample consisted of 76 pregnant women, selected based on inclusion and exclusion criteria. Result and Discussion: The results of the Chi Square statistical test show that there is a relationship between midwife communication and pregnant women's satisfaction with ANC services with a p value of 0.000. Conclusion: There is a relationship between midwife communication and pregnant women's satisfaction with ANC services at the Community Health Center. Researchers suggest that the Cecar Community Health Center should focus on improving the quality of ANC services not only on the technical aspects of pregnancy examinations, but also on improving midwives' communication skills through effective communication training, midwifery counseling, and the implementation of services that are oriented towards the needs of pregnant women.